Plant species composition and local habitat conditions as primary determinants of terrestrial arthropod assemblages - Cynthia Tobisch; Sandra Rojas-Botero; Johannes Uhler; Jörg Müller; Johannes Kollmann; Christoph Moning; Martin Brändle; Martin M. Gossner; Sarah Redlich; Jie Zhang; Ingolf Steffan-Dewenter; Caryl Benjamin; et al. (Oecologia, 2023)
Arthropods respond to vegetation in multiple ways since plants provide habitat and food resources and indicate local abiotic conditions. However, the relative importance of these factors for arthropod assemblages is less well understood. We aimed to disentangle the effects of plant species composition and environmental drivers on arthropod taxonomic composition and to assess which aspects of vegetation contribute to the relationships between plant and arthropod assemblages. In a multi-scale field study in Southern Germany, we sampled vascular plants and terrestrial arthropods in typical habitats of temperate landscapes. We compared independent and shared effects of vegetation and abiotic predictors on arthropod composition distinguishing between four large orders (Lepidoptera, Coleoptera, Hymenoptera, Diptera), and five functional groups (herbivores, pollinators, predators, parasitoids, detritivores). Across all investigated groups, plant species composition explained the major fraction of variation in arthropod composition, while land-cover composition was another important predictor. Moreover, the local habitat conditions depicted by the indicator values of the plant communities were more important for arthropod composition than trophic relationships between certain plant and arthropod species. Among trophic groups, predators showed the strongest response to plant species composition, while responses of herbivores and pollinators were stronger than those of parasitoids and detritivores. Our results highlight the relevance of plant community composition for terrestrial arthropod assemblages across multiple taxa and trophic levels and emphasize the value of plants as a proxy for characterizing habitat conditions that are hardly accessible to direct environmental measurements.

Diverse Effects of Climate, Land Use, and Insects on Dung and Carrion Decomposition - Jana Englmeier; Oliver Mitesser; M. Eric Benbow; Torsten Hothorn; Christian von Hoermann; Caryl Benjamin; Ute Fricke; Cristina Ganuza; Maria Haensel; Sarah Redlich; Rebekka Riebl; Sandra Rojas Botero; et al. (Ecosystems, 2023)
Land-use intensification and climate change threaten ecosystem functions. A fundamental, yet often overlooked, function is decomposition of necromass. The direct and indirect anthropogenic effects on decomposition, however, are poorly understood. We measured decomposition of two contrasting types of necromass, rat carrion and bison dung, on 179 study sites in Central Europe across an elevational climate gradient of 168–1122 m a.s.l. and within both local and regional land uses. Local land-use types included forest, grassland, arable fields, and settlements and were embedded in three regional land-use types (near-natural, agricultural, and urban). The effects of insects on decomposition were quantified by experimental exclusion, while controlling for removal by vertebrates. We used generalized additive mixed models to evaluate dung weight loss and carrion decay rate along elevation and across regional and local land-use types. We observed a unimodal relationship of dung decomposition with elevation, where greatest weight loss occurred between 600 and 700 m, but no effects of local temperature, land use, or insects. In contrast to dung, carrion decomposition was continuously faster with both increasing elevation and local temperature. Carrion reached the final decomposition stage six days earlier when insect access was allowed, and this did not depend on land-use effect. Our experiment identified different major drivers of decomposition on each necromass form. The results show that dung and carrion decomposition are rather robust to local and regional land use, but future climate change and decline of insects could alter decomposition processes and the self-regulation of ecosystems.

Plant richness, land use and temperature differently shape invertebrate leaf-chewing herbivory on plant functional groups - Ute Fricke; Sarah Redlich; Jie Zhang; Cynthia Tobisch; Sandra Rojas-Botero; Caryl S. Benjamin; Jana Englmeier; Cristina Ganuza; Rebekka Riebl; Johannes Uhler; Lars Uphus; Jörg Ewald; et al. (Oecologia, 2022)
Higher temperatures can increase metabolic rates and carbon demands of invertebrate herbivores, which may shift leaf-chewing herbivory among plant functional groups differing in C:N (carbon:nitrogen) ratios. Biotic factors influencing herbivore species richness may modulate these temperature effects. Yet, systematic studies comparing leaf-chewing herbivory among plant functional groups in different habitats and landscapes along temperature gradients are lacking. This study was conducted on 80 plots covering large gradients of temperature, plant richness and land use in Bavaria, Germany. We investigated proportional leaf area loss by chewing invertebrates (‘herbivory’) in three plant functional groups on open herbaceous vegetation. As potential drivers, we considered local mean temperature (range 8.4–18.8 °C), multi-annual mean temperature (range 6.5–10.0 °C), local plant richness (species and family level, ranges 10–51 species, 5–25 families), adjacent habitat type (forest, grassland, arable field, settlement), proportion of grassland and landscape diversity (0.2–3 km scale). We observed differential responses of leaf-chewing herbivory among plant functional groups in response to plant richness (family level only) and habitat type, but not to grassland proportion, landscape diversity and temperature—except for multi-annual mean temperature influencing herbivory on grassland plots. Three-way interactions of plant functional group, temperature and predictors of plant richness or land use did not substantially impact herbivory. We conclude that abiotic and biotic factors can assert different effects on leaf-chewing herbivory among plant functional groups. At present, effects of plant richness and habitat type outweigh effects of temperature and landscape-scale land use on herbivory among legumes, forbs and grasses.

Development and application of a low-cost rapid assessment system for coastal benthic habitats - Caryl S. Benjamin; Patrick Lawrence P. Cadeliña; Aletta T. Yñiguez; Cesar L. Villanoy (Environmental Monitoring and Assessment, 2019)